PATH-43. RETROSPECTIVE RECLASSIFICATION OF ADULT GLIOMAS FROM A MANITOBA PATIENT COHORT ACCORDING TO THE WHO 2016 GUIDELINES. (5th November 2018) - Norquay, Amy; Pitz, Marshall; Lambert, Pascal; Galloway, Katie; Krawitz, Sherry
Abstract: The new WHO 2016 classification of CNS tumours classifies adult gliomas based on the presence or absence of two key molecular markers, IDH mutation and 1p/19q co-deletion. We applied the new criteria to Manitoba glioma patients diagnosed between 2013–2016 with the objective of assessing the distribution of molecular markers among the entire population of glioma patients, assess the prognostic power of the molecular markers, and evaluate the impact of the new classification system on patients. In total, 203 patients were included, and the majority of gliomas were IDH wild type (81.8%). Among the IDH mutant tumours, 9.9% were 1p/19q intact and/or ATRX loss, and 8.4% were 1p/19q co-deleted. The WHO 2016 was impactful on patients such that roughly one third were reclassified into 2016 diagnostic categories with different prognoses. Molecular markers were marginally better than grade at predicting progression free survival, however, the predictive power of the model was improved when molecular markers and grade were included in the same model.